simplify using BODMAS rule [-10-3×{4-(-4)}×{3-(5-3)}]
Answers
Answer:
-34
Step-by-step explanation:
[-10-3×{4-(-4)}×{3-(5-3)}]
Solve the bracket first according to BODMAS rule
= [-10 - 3 × { 4- (- 4)} × {3 - (2)}]
= [-10 - 3 × { 4- (- 4)} × { 1 }]
= [-10-3 × { 4- (- 4)} × { 1 }]
= [-10-3 × {4 + 4} ]
= [-10-3 × { 8} ]
= [ -10-3 × 8 ]
= [ - 10 - 24 ]
= -34
Answer:
=> -34
Step-by-step explanation:
Given that:-
To find:- The value of the expression
For simplifying the expression, we have to use the BODMAS concept.
It is the rule used to remember the order of operations that is followed while solving expressions in mathematics.
where,
B= bracket
O= order of power or rules
D= division
M= multiplication
A= addition
S= subtraction
As we have,
=>
Simplifying it further, we get
=>
=>
=>
=>
=>
=>
=>
=>
Hence, the required solution is -34.